2014
DOI: 10.1155/2014/681073
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Propensities and Phytochemical Profile ofVangueria madagascariensisJ. F. Gmelin (Rubiaceae): An Underutilized Native Medicinal Food Plant from Africa

Abstract: Vangueria madagascariensis (VM), consumed for its sweet-sour fruits, is used as a biomedicine for the management of diabetes and bacterial infections in Africa. The study aims to assess the potential of VM on α-amylase, α-glucosidase, glucose movement, and antimicrobial activity. The antioxidant properties were determined by measuring the FRAP, iron chelating activity, and abilities to scavenge DPPH, HOCl, ∙OH, and NO radicals. Leaf decoction, leaf methanol, and unripe fruit methanol extracts were observed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…However, there was a significant and moderate correlation between proanthocyanidin contents and log(1/IC 50 ) values ( R = 0.6) without the extreme values. Some studies have demonstrated a positive correlation between α ‐glucosidase‐inhibitory activities and proanthocyanidin contents, whereas others have reported no positive relationship . In our study, α ‐glucosidase‐inhibitory activities and proanthocyanidin contents might be related.…”
Section: Resultscontrasting
confidence: 43%
“…However, there was a significant and moderate correlation between proanthocyanidin contents and log(1/IC 50 ) values ( R = 0.6) without the extreme values. Some studies have demonstrated a positive correlation between α ‐glucosidase‐inhibitory activities and proanthocyanidin contents, whereas others have reported no positive relationship . In our study, α ‐glucosidase‐inhibitory activities and proanthocyanidin contents might be related.…”
Section: Resultscontrasting
confidence: 43%
“…[35][36][37][38] On the other hand, several studies showed lower correlation between antioxidant and enzyme inhibitory effects. 39,40 At this point, it seems to the contradictory results are most probably due to differences in chemical structure, functional groups, and in the methodology used. Up to date, there have been a few reports on enzyme inhibitory effects of AQs.…”
Section: Discussionmentioning
confidence: 99%
“… MAPRI-H.Y.6/005 17 Vangueria madagascariensis J.F.Gmel. Rubiaceae Fruit El-Kirkir Used in the treatment of diabetes mellitus and bacterial infections [ 61 ]. MAPRI-H.W.45/95 18 Ziziphus spina-christi L. Rhamnaceae Roots Sidir Used in the treatment of gonorrhea, fever, as anti-spasmodic and anti-purgative [ 17 , 62 ].…”
Section: Introductionmentioning
confidence: 99%